MODEL JARINGAN PEMANGKU KEPENTINGAN EKOSISTEM AGILE - Puti Retno Ali; Suprihatin Suprihatin; Nastiti Siswi Indrasti (Jurnal Teknologi Industri Pertanian, 2023)
Current business practices are no longer relevant in the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) environment. VUCA reflects the speed of change, uncertainty, complexity, and ambiguity in the business world. Companies need to be agile to adapt to the prevailing VUCA situations. This study aims to provide an understanding of business agility from the perspective of stakeholder needs through a model. The method used is a focus group discussion involving the relevant stakeholders, with a case study conducted in an integrated chicken meat company. The results of the study reveal that an agile ecosystem stakeholder network model consists of seven stakeholder elements: academia, business, community, government, media, financial institutions, and customers as the core element of the model. The "customer" stakeholder element is the most crucial, while the other stakeholder elements influence each other in their actions, with their ultimate goal of meeting customer needs. By placing the customer element at the core of the model, the business environment can be aligned and better outcomes can be achieved. The recommendation derived from this study is the explicit formulation of company strategies in achieving business agility. Keywords: agile, business agility, customer, model, stakeholder